Self- and Other-Focused Emotional Intelligence, Situational Emotional Understanding, and Experience of Loss - Dirzyte, Aiste; Patapas, Aleksandras; Židonis, Žilvinas; Valantinas, Antanas; Dubauskiene, Šarune (Journal of Intellectual Disability - Diagnosis and Treatment, 2021)
The links between emotional intelligence and loss are under-researched, even though a lot of studies have investigated the psychological outcomes of traumatic experiences. Many people suffered multiple losses during the COVID-19 pandemic, including a loss of job, money, support services, or loved ones. The loss of a loved one might result in severe psychological trauma, and research suggests that early-life trauma relates to numerous forms of emotion dysregulation, including stress-reactivity. The consequences of loss for people with special needs deserve special attention since it often means not only the loss of a loved one but also the usual way of life. Thus, it is essential to analyze various aspects of loss experience, including the impact on emotional regulation, to reduce the harmful consequences of the COVID-19 pandemic. The purpose of this research was to examine emotional intelligence in groups of those who have a recent experience of loss and those who have not and to establish the impact of the experience of loss on the human psyche and mental health. We have analyzed the results of a simple random sample of gymnasium students (n=362). We hypothesized that the recent loss of a loved one diminishes the ability to understand self and other focused emotions as well as situational emotions. The survey has revealed that respondents who experienced the loss of a loved one understood better how individuals felt in the presented situations than those who did not have such experience. The premise that people who have experienced the loss of a loved one have a lower understanding of emotions than their peers who did not have such an experience has not been confirmed.